Course of Domestic Abuse Among Chicago's Elderly: Risk Factors, Protective Behaviors, and Police Intervention, 2006-2009 - Amendola, Karen L. ([Verlag nicht ermittelbar], 2013)
The study was conducted to examine if and how risk factors and protective behaviors affect the course of elder abuse over time, and the role of police in intervening with elderly victims of domestic abuse and/or neglect. It also examined the prevalence rates for various types of abuse using a stratified sample of Chicago's elderly population. The study involved in-depth interviews with 328 elderly (aged 60 and over) residents of Chicago from three sample groups: (1) 159 community nonvictims; (2) 121 community victims; and (3) a police sample consisting of 48 elderly victims who had been visited by trained domestic violence/senior citizen victimization officers in the Chicago Police Department. The interviews were conducted using a survey instrument designed to assess victimization. The survey included questions about various characteristics and risk factors associated both with victims and perpetrators of abuse and/or neglect, specific types of abuse, and protective behaviors of victims. Victimization was examined twice over a 10-month period to evaluate the course of abuse over time. The efficacy of police intervention was also examined.